Impact of the COVID-19 induced lockdown measures on [Formula: see text] concentration in USA - Ghosal, Rahul (Atmos Environ (1994), 2021)
In 2020, most countries around the world have observed varying degrees of public lockdown measures to mitigate the transmission of SARS-CoV-2. As an unintended consequence of reduced transportation and industrial activities, air quality has dramatically improved in many major cities around the world. In this paper, we analyze the environmental impact of the lockdown measures on [Formula: see text] concentration levels in 48 core-based statistical areas (CBSA) of the United States, during the pre and post-lockdown period of January to June 2020. We model the effect of lockdown on the [Formula: see text] concentration in different CBSAs while adjusting for various meteorological factors like temperature, wind-speed, precipitation and snow. Linear mixed effects models and functional regression methods with random intercepts are employed to capture the heterogeneity of the effect across different regions. Our analysis shows there is a statistically significant reduction in levels of [Formula: see text] across most of the regions during the lock-down period, although interestingly, this effect is not uniform across all the CBSAs under consideration.